O Teatro de Arena na arena do Brasil - Maria Christina da Silva (2008)
This work aims to contribute to the reflection of the possible connections between History and Theater. It considers the analysis of Teatro de Arenas utopias during the decade of 1950 in Brazil, with the intent to discuss some moments of our contemporary history. Starting from approaches which blend drama and historical process, two playsproduced and staged by the first time for this company will be studied: Eles Não Usam Black-Tie (1958), by Gianfrancesco Guarnieri, and Chapetuba Futebol Clube (1959), by Oduvaldo Vianna Filho. In the first chapter, the Teatro de Arena will be analysed from the point of view of their critical approaches; in the second, relations between thoseplays and history. In the third, will be done a study over the process of writing and stage, looking for rescue the contemporary and importance of Teatro de Arena and its role on Brazilian drama.